Development of a multi-epitope spike glycoprotein vaccine to combat SARS-CoV-2 using the bioinformatics approach - Aamir Shehzad; Christijogo Sumartono; Jusak Nugraha; Helen Susilowati; Andi Yasmin Wijaya; Hafiz Ishfaq Ahmad; Muhammad Kashif; Wiwiek Tyasningsih; Fedik Abdul Rantam (GarVal Editorial Ltda., 2022)
Context: The current COVID-19 pandemic has significantly impacted health and socio-economic status worldwide. The only way to combat this situation is to develop an effective vaccine and immunize people around the globe. Aims: To construct a multi-epitope spike glycoprotein-based vaccine from the SARS-CoV-2 Surabaya isolate using a bioinformatics approach. Methods: The spike protein was submitted to IEDB, VaxiJen, AllerTOP, and ToxinPred webservers to predict antigenic, non-allergic, non-toxic, B- and T-cell epitopes. To develop a multi-epitope vaccine, an adjuvant cholera toxin B subunit was linked to B-cell and B-cell with T-cell through EAAAK and GPGPG linkers, respectively. The designed vaccine 3D structure development, refinement, and validation were done through PHYRE2, Galaxy Refine, and RAMPAGE webservers. Moreover, the Cluspro-2.0 webserver was used for the molecular docking of the vaccine designed with TLR3. The vaccine+TLR3 complex was docked with Surfactant protein A as a control to validate the docking results. Finally, immune-simulation and in silico cloning of the vaccine were carried out by C-ImmSim webserver and SnapGene software, respectively. Results: A multi-epitopic vaccine containing B and T-cell was developed using 392 amino acids with a molecular weight of 40825.59 Da. The docking and immunogenicity results of the vaccine met all established parameters for constructing a quality vaccine. Furthermore, the optimized sequence of the vaccine was successfully cloned in expression vector pET 28 a (+) that yielded a colon of 2724 bp. Conclusions: The vaccine's immunogenicity demonstrates its effectiveness against SARS-CoV-2 infection. Further confirmatory testing may therefore be performed as soon as possible in the public interest.